2002
DOI: 10.1364/ao.41.004585
|View full text |Cite
|
Sign up to set email alerts
|

Thermally and electrically switchable gratings based on polymer-ball-type polymer-dispersed liquid-crystal films

Abstract: We focus on the fabrication and study of controllable holographic gratings based on azo-dye-doped and undoped polymer-ball-type polymer-dispersed liquid-crystal films. Experimental results indicate that the next step of photopolymerization of the sample with the illumination of Ar+ laser beams after UV curing causes a latent density grating to be recorded. This grating is formed by a selective secondary photopolymerization. Heating and applying a voltage change the structure of the liquid crystal and induce th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 14 publications
(12 reference statements)
0
6
0
Order By: Relevance
“…Neglecting the weak dependence on n of the square root in the denominator, we expand sin(pn) of expression (10) up to the linear term, and get the following result:…”
Section: Comparison With Experimental Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neglecting the weak dependence on n of the square root in the denominator, we expand sin(pn) of expression (10) up to the linear term, and get the following result:…”
Section: Comparison With Experimental Resultsmentioning
confidence: 99%
“…The common goal of this kind of applications is to reach a high diffraction efficiency in gratings fabricated by simple and cheap processes. During the last decade, a lot of work has been carried out concerning the characterization of morphology and diffraction efficiency [7][8][9], as well as switching properties [10,11,5] of such devices. In order to obtain high diffraction efficiency and good optical quality gratings, it is necessary to achieve a sharp and uniform fringe morphology; many attempts have been made therefore in order to avoid those optical inhomogeneities (produced by nematic droplets) which have the same spatial scale as the wavelength of the diffracted radiation.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25] Polymer morphologies in the lms can be divided into polymer-network-type and polymerball-type. [26][27][28] By optimizing the light scattering performance, PDLC lms with high transmittance can be applied in solar cells, organic light emitting diodes (OLEDs) and other optical electrical devices. Yang et al have demonstrated a novel light enhancing lm based on PDLCs that can increase the light efficiency of OLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many basic studies on optical behavior [28][29][30][31], electro-optic switching [32], liquid crystal ordering [33], and polymer morphologies [34][35][36]. Within the last few years, a number of new configurations have been reported, such as those based on polymer networks [37][38][39], polarization independent switching configurations [40], smectic-A phases [41], two-photon induced polymerization renditions [42], tunable reflection modes [43], specialized holographic methods [44][45][46], diffuse reflection modes [47], azo-dye doped PDLCs [48,49], thermal switching modes [50], and total internal reflection configurations [51]. Figure 1(a) illustrates how a red, green, blue H-PDLC stack (electrically switchable color filter stack) can be used in digital imaging using a single CCD [21] and Figure 1(b) illustrates the operation of a four-channel add-drop filter for telecommunication applications [22].…”
Section: Introductionmentioning
confidence: 99%